Factor Analysis of the Mystical Experience Questionnaire: A Study of Experiences Occasioned by the Hallucinogen Psilocybin - MacLean, Katherine A.; Leoutsakos, Jeannie-Marie S.; Johnson, Matthew W.; Griffiths, Roland R. (Journal for the scientific study of religion, 2012)
A large body of historical evidence describes the use of hallucinogenic compounds, such as psilocybin mushrooms, for religious purposes. But few scientific studies have attempted to measure or characterize hallucinogen-occasioned spiritual experiences. The present study examined the factor structure of the Mystical Experience Questionnaire (MEQ), a self-report measure that has been used to assess the effects of hallucinogens in laboratory studies. Participants (N = 1,602) completed the 43-item MEQ in reference to a mystical or profound experience they had had after ingesting psilocybin. Exploratory factor analysis of the MEQ retained 30 items and revealed a four-factor structure covering the dimensions of classic mystical experience: unity, noetic quality, sacredness (F1); positive mood (F2); transcendence of time/space (F3); and ineffability (F4). MEQ factor scores showed good internal reliability and correlated with the Hood Mysticism Scale, indicating convergent validity. Participants who endorsed having had a mystical experience on psilocybin, compared to those who did not, had significantly higher factor scores, indicating construct validity. The four-factor structure was confirmed in a second sample (N = 440) and demonstrated superior fit compared to alternative models. The results provide initial evidence of the validity, reliability, and factor structure of a 30-item scale for measuring single, hallucinogen-occasioned mystical experiences, which may be a useful tool in the scientific study of mysticism.